Energy and exergetic performance analysis of a hybrid solar multi-stage Brayton cycle with different working fluids (2023)
An energy and exergy model for a hybrid multi-stage Brayton cycle solar thermal plant is presented, incorporating an arbitrary number of compression stages with intermediate cooling and expansion with reheating. In hybrid operation, the cycle receives thermal energy from a solar concentration system of a heliostat field and a central tower complemented by reheaters and an external main combustion chamber of natural gas. The proposed model considers the irreversibility of the plant’s components, and direct solar radiation is estimated with the Daily Integration Approach model. The model is validated and implemented with the Solugas experimental plant parameters and is applied in Barranquilla, Colombia. Additionally, this work presents a comparative analysis of different plant configurations using air, carbon dioxide and helium as working fluids. Comparing the power, the energetic and exergetic efficiencies, and the destruction of exergy on an average day of the year, the maximum points of these variables are also found as a function of the pressure ratio. Observing that the twocompression-one-expansion CO2 cycle presents maximum fuel conversion rates and the slightest destruction of total exergy.